(untitled) (Annals of Medical Research, 2022)
Aim: Aortic dissections emerge as severe pathologies reqiuring early diagnosis and immediate surgical intervention is mandatory in acute Type A aortic dissection, however, there are still controversies regarding the appropriate approach. The present study aims to demonstrate the effects of valve resuspension with supracoronary tube graft replacement on aortic valve insufficency in acute Type A aortic dissection. Material and Methods: The study was conducted on 108 patients who had supracoronary aortic replacement with suspension for acute Type A aortic dissection and discharged from the hospital with cure between January 1997 and January 2014. The patients were evaluated for aortic valve function by transthoracic echocardiography at the postoperative 6th and 12th months. Results: Gender distribution was 31 (29%) females and 77 (71%) males, their mean age being 53.24 ±11,3 years old. In the present study, valve function measured with preoperative and postoperative 6th and 12th months transthoracic echo revealed a significant decrease in terms of aortic valve insufficiency. After surgery, no patient required a reoperation for valve insufficency within the 1st year. Conclusion: All these have demonstrated that in the treatment of acute Type A aortic dissection, aortic insufficiency is not a restrictive factor for chosing the resuspension with supracoronary tube graft replacement method in patients without any organic disease of the aortic valve and root aneursym and in whom the rupture is not progressing proximally to affect coronary entries. By using the this method aortic dissections can treated with good results while native valve preserved.